Una propuesta para la mejora de la calidad de la educación virtual - Guzmán, Claudia; Campos Montalvo, Elena; Ambrosino, Alejandra; Valeiras, Nora (2024)
Fil: Guzmán, Claudia. Universidad Nacional de Córdoba, Argentina.